Sodium-calcium exchanger-3 regulates pain ‘‘wind- up’’: From human psychophysics to spinal mech- anisms (2022)
ABSTRACT: Repeated application of noxious stimuli leads to a progressively increased pain perception; this temporal sum-mation is enhanced in and predictive of clinical pain disorders. Its electrophysiological correlate is ‘‘wind-up,’’ in which dorsal horn spinal neurons increase their response to repeated nociceptor stimulation. To understand the genetic basis of temporal summation, we undertook a GWAS of wind-up in healthy human volunteers and found significant association with SLC8A3 encoding sodium-calcium exchanger type 3 (NCX3). NCX3 was expressed in mouse dorsal horn neurons, and mice lacking NCX3 showed normal, acute pain but hypersensitivity to the second phase of the formalin test and chronic constriction injury. Dorsal horn neurons lacking NCX3 showed increased intracellular calcium following repetitive stimulation, slowed calcium clearance, and increased wind-up. Moreover, virally mediated enhanced spinal expression of NCX3 reduced central sensitization. Our study highlights Ca2+ efflux as a pathway underlying temporal summation and persistent pain, which may be amenable to therapeutic targeting.